PENGARUH FAKTOR-FAKTOR KEPEMIMPINAN SITUASIONAL TERHADAP PRESTASI KERJA PEGAWAI BADAN PEMBERDAYAAN MASYARAKAT DAN PEMERINTAHAN DESA - jurnalmap map; Dian Anggadewi Setyabekti; Nugroho Mardi Wibowo; Soenarmi ÔÇì (MAP (Jurnal Manajemen dan Administrasi Publik), 2019)
ABSTRACT This study aims to describe and analyze the influence of partial and simultaneous factors of leadership style in the Community Empowerment and Village Government Board of Bojonegoro Regency. This research method uses a quantitative method with a population of 34 people. The sampling method in this study used a total sampling of 34 people. The results of data analysis showed situational leadership style consisting of directive, consultative, participatory, delegative had a significant effect on the work performance of employees of the Community Empowerment Agency and Village Government of Bojonegoro Regency. Partially situational leadership style factors which consist of directive, consultative, participatory, delegative have a significant effect on the work performance of employees of the Community Empowerment Agency and Village Government of Bojonegoro Regency. Among the situational leadership style factors which consist of directive, consultative, participatory, delegative, the most dominant of employee performance is the directive leadership style variable. Keywords: situational leadership, work performance